Self Potential untuk Pendugaan Reservoir Sistem Panas Bumi Blawan - Siti Diah Ayu Febriani (Jurnal Fisika FLUX, 2020)
Self-Potential methods that have advantages in providing more extensive and integrated information to better ensure that geothermal areas have potential geothermal resources. This study discusses the geothermal system in the Ijen volcano area based on the value of resistivity and potential different from the subsurface structure. The stages in the implementation of research programs are (1) literature study, carried out to obtain accurate and up-to-date information, (2) data retrieval, carried out to obtain primary and secondary data, (3) data search, data processing, and data interpretation, carried out using Res2div and Surfer software to obtain subsurface structure mapping (4), evaluation, was carried out as a monitoring of geothermal resource potential mapping research. The modeling results were obtained from the subsurface layer in Blawan geothermal manifestation consisting of 3 zones with upper resistivity zones (> 10 ohm to 50 ohm meters), reservoir zones (> 50 ohm meters to 100 ohm meters) and heat source zones (> 100 ohm meters, based on the isopotential contour map, that the Blawan region is a destructive zone.